Pengaruh Leverage, Bonus Plan, Ukuran Perusahaan, dan Profitabilitas pada Praktik Perataan Laba - Anggi Adeliana Dewi, Made; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 26 No 1 (2019)DO - 10.24843/EJA.2019.v26.i01.p03, 2019)
The study was conducted on consumer goods industry companies for the period 2013-2017. The number of research samples is 165 observations chosen by non probability sampling method, namely purposive sampling. The data analysis technique uses logistic regression analysis. Based on the analysis, results can be obtained namely leverage does not affect the income smoothing practice; bonus plan ha s positive effect on income smoothing practices; company size has negative effect on income smoothing practices; and 4) profitability has no effect on income smoothing practices. The implications of this research can be divided into two types, namely theoretical and practical implications. Theoretical implications that can be a reference source of research relating to income smoothing practices and can support positive keaganen theory and accounting theory, while the practical implication is a consideration for investors in making investment decisions. Keywords : leverage, bonus plan, company size, profitability, income smoothing practice